The Old English metrical calendar (Menologium) (D.S. Brewer, 2015)
The late tenth-century Old English Metrical Calendar (traditionally known as Menologium) summarises, in the characteristic heroic diction and traditional metre of Old English poetry, the majorcourse of the Anglo-Saxon liturgical year. It sets out, in a methodical structure based on the basic temporal framework of the solar/natural year, the locations of the major feasts widely observed inlate Anglo-Saxon England. Such a work could have been a practical timepiece for reading the dates of the Anglo-Saxon Chronicle, for which it serves as a kind of prologue in the manuscript. The clearlydomestic perspective of the poem, which fits in the manuscript context, is also noteworthy, while the poem also reveals various interesting characteristics in its grammar, vocabulary and prosody. This is the first full modern edition of the poem, and is accompanied by a facing translation. The introduction provides an extensive discussion of matter, content, style, and context, while the commentary offers further information. The volume also includes the texts and translations of a number of analogous works. Kazutomo Karasawa is Professor of English philology at Komazawa University, Tokyo.
Title from publisher's bibliographic system (viewed on 04 Jun 2021)
Keywords: Christian martyrs